Pengaruh Eco-Labeling Terhadap Persepsi Kualitas Konsumen Dalam Mendukung Konsumsi Berkelanjutan (SDG 12) Pada Produk The Body Shop Di Kota Bogor - Zahra , Rizka Aulia; Sulaiman, Anwar; Suwandi , Siti Isella Oktavina; Cahya , Danar; Maulana, Zidan; Mutaqin, Eza Akmal; Ardiansyah, Riko (AGUSPATI Research Institute, 2026)
The increasing awareness of environmental issues among consumers highlights the importance of providing product information that represents sustainability values, one of which is through eco-labeling. This quantitative study aims to examine the significance of the effect of eco-labeling on consumers’ perceived quality in supporting sustainable consumption (SDG 12) of The Body Shop products in Bogor City. This study is grounded in the concept of sustainable marketing, which views eco-labels as informational signals that mediate consumers’ evaluations of product quality. The research employed a quantitative approach by collecting primary data through questionnaires distributed to consumers of The Body Shop in Bogor City. The research instrument was developed based on indicators of eco-labeling and perceived quality and was tested for validity and reliability. The collected data were analyzed using simple linear regression, along with the coefficient of determination and hypothesis testing. The results indicate that eco-labeling has a positive and significant effect on consumers’ perceived quality. These findings confirm that eco-labeling functions as an effective communication tool in conveying product sustainability values, thereby strengthening perceived quality and encouraging more responsible consumption patterns in line with the objectives of SDG 12.